Borders and Barriers: challenges of Fisheries Management and Conservation in Open Systems. (11th January 2017) - Siddons, S. F.; Pegg, M. A.; Klein, G. M.
Abstract: Large rivers often bisect geopolitical boundaries where management goals may be at odds for a shared fishery, creating fragmented management zones. Fragmentation due to physical barriers may further impact the fishery by reducing fish passage. Our goal was to estimate basin‐wide parameters (i.e. movement, survival and capture probabilities) of a large‐river species known to move throughout watersheds. We tagged13 892 Channel Catfish in the Red River of the North (Red River) and Lake Winnipeg in Manitoba, Canada, and collected 553 recaptures. We estimated 2.2% of catfish are moving from the Red River to Lake Winnipeg each month and 9.4%, primarily large (>600 mm) individuals, moved upstream through a dam (monthly). Approximately 5.6% of catfish moved to the USA each month, and only one fish returned. Our results suggest the lower reaches of the Red River may be a source population for the USA, where survival is lower, and Lake Winnipeg. The complex movements of Channel Catfish throughout the Red River, across barriers and international boundaries, suggest conservation and management of fish populations should be watershed wide. Copyright © 2017 John Wiley & Sons, Ltd.